Distance Learning Training with Google Classrom at SMAN 1 Sibabangun Regency Central Tapanuli - Jhonas Dongoran; Bronika Septiani Sianturi; Zulmawati - (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
In distance learning, the role of technology is needed to be able to connect with one another. One of the learning media that can be used for distance learning is Google Classroom. Mastery of technology and information for teachers at SMAN 1 Sibabangun, Central Tapanuli Regency is very necessary in this distance learning. The effort that must be made by a teacher in providing distance learning is to create media such as Google Classroom. Through Google Classroom, teachers can create classes for teaching and learning activities and students can take classes. In this training, teachers can give assignments, provide assessments of student assignments, import learning materials, and also make quizzes for students. The result of the service carried out is that the teacher is able to make learning media using google classroom so that distance learning can run more effectively. With the dedication that is carried out, it can realize the vision and mission of the SMAN 1 Sibabangun school, Central Tapanuli Regency. The results of the questionnaire from this community service activity are very good at 42.94%, good at 48.89%, enough at 7.6%, less at 0.55%, and very poor at 0.01%.